Obesity, Psychological Distress, and Resting State Connectivity of the Hippocampus and Amygdala Among Women With Early-Stage Breast Cancer - Donofry, Shannon D.; Lesnovskaya, Alina; Drake, Jermon A.; Ripperger, Hayley S.; Gilmore, Alysha D.; Donahue, Patrick T.; Crisafio, Mary E.; Grove, George; Gentry, Amanda L.; Sereika, Susan M.; Bender, Catherine M.; Erickson, Kirk I. (Frontiers in Human Neuroscience, 2022)
Objective: Overweight and obesity (body mass index [BMI]≥25kg/m2) are associated with poorer prognosis among women with breast cancer, and weight gain is common during treatment. Symptoms of depression and anxiety are also highly prevalent in women with breast cancer and may be exacerbated by post-diagnosis weight gain. Altered brain function may underlie psychological distress. Thus, this secondary analysis examined the relationship between BMI, psychological health, and resting state functional connectivity (rsFC) among women with breast cancer. Methods: The sample included 34 postmenopausal women newly diagnosed with Stage 0-IIa breast cancer (Mage=63.59±5.73) who were enrolled in a six-month randomized controlled trial of aerobic exercise vs. usual care. At baseline prior to randomization, whole-brain analyses were conducted to evaluate the relationship between BMI and seed-to-voxel rsFC of the hippocampus and amygdala. Connectivity values from significant clusters were then extracted and examined as predictors of self-reported depression and anxiety. Results: Mean BMI was in the obese range (M=31.83±6.62). For both seeds examined, higher BMI was associated with lower rsFC with regions of prefrontal cortex (PFC), including ventrolateral PFC (vlPFC), dorsolateral PFC, and superior frontal gyrus (z range=2.85-4.26). Hippocampal connectivity with the vlPFC was negatively correlated with self-reported anxiety (β=0.47, p<0.01). Conclusions: Higher BMI was associated with lower hippocampal and amygdala connectivity to regions of PFC implicated in cognitive control and emotion regulation. BMI-related differences in hippocampal and amygdala connectivity following a recent breast cancer diagnosis may relate to future worsening of psychological functioning during treatment and remission. Additional longitudinal research exploring this hypothesis is warranted.